The Effect of Tofu Dregs Compost and NPK Fertilizer the Growth and Production of Purple Eggplan (Solanum melongena L.) - Arnis En Yulia; M Amrul Khoiri; Sri Yoseva; Nuraida Nuraida (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2022)
The research was aimed to see the effect interaction of giving tofu dregs compost and npk fertilizer to get the right dose towards growth and the highest production of purple eggplant. The research was conducted at Experimental Garden, Faculty of Agriculture, Riau University, Pekanbaru. The research was conducted for 5 months, from february to june 2020. The reasearch was conducted experimentally in 2 factors. The first factor was the of tofu waste compost consists of 3 levels (0, 10 and 20 ton.ha-1). The second factor was the of NPK fertilizer (0, 100 and 150 kg.ha-1) which consist of nine treatments combination. The observed parameterswere the height of the plant (cm), the days of flowering (days), the days of harvesting (days), the fruit length (cm), the fruit diameter (cm), the number of fruits per plant (fruit), the fruit weight per fruit (g), the fruit weight per plant (g) and the fruit weight with plot (g). The data in this research was analyzed in using variance and followed by Duncan's multiple distance test at 5% level. The results showed that tofu waste compost and NPK fertilizer increased the growth of eggplant such as the height of the plant, the days of flowering, the days of harvesting, the number of fruits per plant, the fruit length, the fruit weight per fruit, the fruit weight per plant and the fruit weight with plot and does not increase fruit diameter. The giving tofu waste compost at a dose 20 ton.ha-1 and NPK fertilizer 150 kg.ha-1 gave the best eggplant growth and production until the plants were 90 DAP